Nanoremediation: Nanomaterials and Nanotechnologies for Environmental Cleanup - Del Prado-Audelo, M. L.; García Kerdan, I.; Escutia-Guadarrama, L.; Reyna-González, J. M.; Magaña, J. J.; Leyva-Gómez, G. (Frontiers in Environmental Science, 2021)
Different global events such as industrial development and the population increment have triggered the presence and persistence of several organic and inorganic contaminants, representing a risk for the environment and human health. Consequently, the search and application of novel technologies for alleviating the challenge of environmental pollution are urgent. Nanotechnology is an emerging science that could be employed in different fields. In particular, Nanoremediation is a promising strategy defined as the engineered materials employed to clean up the environment, is an effective, rapid, and efficient technology to deal with persistent compounds such as pesticides, chlorinated solvents, halogenated chemicals, or heavy metals. Furthermore, nanoremediation is a sustainable alternative to eliminate emerging pollutants such as pharmaceutics or personal care products. Due to the variety of nanomaterials and their versatility, they could be employed in water, soil, or air media. This review provides an overview of the application of nanomaterials for media remediation. It analyzes the state of the art of different nanomaterials such as metal, carbon, polymer, and silica employed for water, soil, and air remediation.